Circular RNA Involved in the Protective Effect of Malva sylvestris L. on Myocardial Ischemic/Re-Perfused Injury - Xiao, Yongzhi; Oumarou, Diafara Boureima; Wang, Shuang; Liu, Yingzhe (Frontiers in Pharmacology, 2020)
Ischemic heart disease is a major health challenge worldwide with high mortality and morbidity rates. Malva sylvestris L. (MS) has laxative, emollient, and anti-inflammatory properties, and has been used for medicinal and therapeutic purposes. In this study, we aimed at elucidating the mechanism of MS against ischemia-reperfusion (I/R)-induced injury in vivo and in vitro. The I/R animal model in rats and oxygen glucose deprivation /re-oxygenation (OGD/Re) model in H9c2 cells were used in this study. MS was used to pre-treat the rats and cells. Electrocardiogram, histology staining, qPCR, ELISA, CCK-8, and circRNA microarray were performed. We found that pre-treatment with MS extract attenuate OGD/Re-induced cell apoptosis and cell viability inhibition in H9c2 cells. In addition, pre-treatment with MS protected against I/R injury in vivo. The protective effects of MS pre-treatment were associated with inflammatory genes expression and cytokines release. Further mechanistic investigation revealed that MS protected cardiomyocytes through regulating circular RNA (circRNA). We identified a novel circRNA circ003593 that mediated the protective role of MS in vitro through NLRP3 complex, which was associated with reperfusion injury salvage kinase (RISK) signaling pathway. Conclusion: this study is the first time to demonstrate the protective role of MS on I/R injury. Our findings reveal a novel circRNA circ003593-mediated the protective role of MS through NLRP3 inflammasome. Circ003593 may serve as a potential therapeutic target for ischemic heart diseases.